MTHFR C677T polymorphism analysis: A simple, effective restriction enzyme‐based method improving previous protocols. Issue 5 (13th March 2019) - Antonaros, Francesca; Olivucci, Giulia; Cicchini, Elena; Ramacieri, Giuseppe; Pelleri, Maria Chiara; Vitale, Lorenza; Strippoli, Pierluigi; Locatelli, Chiara; Cocchi, Guido; Piovesan, Allison; Caracausi, Maria
Abstract: Background: 5, 10‐Methylentetrahydrofolate reductase (MTHFR) C677T polymorphism is one of the most studied genetic variations in the human genome. Polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) is one of the most used techniques to characterize the point mutations in genomic sequences because of its suitability and low cost. The most widely used method for the MTHFR C677T polymorphism characterization was developed by Frosst et al. (1995) but appears to have some technical limitations. The aim of this study was to propose a novel PCR‐RFLP method for the detection of this polymorphism. Methods: In order to retrieve all published articles possibly describing any PCR‐RFLP methods useful to analyze MTHFR C677T polymorphism, we performed systematic queries on PubMed, using a combination of Boolean operators (AND/OR) and MeSH terms. Amplify software was used in order to design a new primer pair following the optimal standard criteria. Primer‐BLAST software was used to check primer pair's biological specificity. Results: The analysis of previous literature showed that PCR‐RFLP method remains the most used technique. None of the 108 primer pairs described was ideal with regard to main accepted primer pair biochemical technical parameters. The new primer pair amplifies a DNA‐fragment of 513 base pair (bp) that, in the presence of the polymorphism, is cut by Hin f I enzyme in two pieces of 146 bp and 367 bp and clearly visible on 2% agarose gel. The level of expertise and the materials required are minimal and the protocol takes one day to carry out. Conclusion: Our original PCR‐RFLP strategy, specifically designed to make the analysis optimal with respect to PCR primers and gel analysis, fits the ideal criteria compared to the widely used strategy by Frosst et al (1995) as well as any other PCR‐RFLP strategies proposed for MTHFR C677T polymorphism genotyping to date. Abstract : The aim of this study was to propose a novel polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) method for the detection of the 5, 10‐Methylentetrahydrofolate reductase ( MTHFR ) C677T polymorphism. A new primer pair was designed to make the method optimal with respect to existing strategies for genotyping. The primer pair amplifies a DNA‐fragment of 513 base pair (bp) that, in the presence of the polymorphism, is cut by Hin f I enzyme in two pieces of 146 bp and 367 bp and clearly visible on 2% agarose gel. The level of expertise and the materials required are minimal and the protocol takes one day to carry out.